Fc-optimized CD276 antibody enhances NK cell activation against non-small cell lung cancer - Stefańczyk, Sylwia A.; Kaiser, Xenija; Hagelstein, Ilona; Holzmayer, Samuel; Zekri, Latifa; Jung, Susanne; Märklin, Melanie (Frontiers in Immunology, 2025)
Non-small cell lung cancer (NSCLC) is one of the most common and lethal cancers worldwide, with a poor prognosis for many patients, especially in advanced stages. The development of immune checkpoint inhibitors (ICIs) has transformed treatment strategies for NSCLC. ICIs targeting PD-1/PD-L1 have shown substantial bene!t, but these therapies are not effective in all patients and are also associated with significant side effects. One promising target for NSCLC immunotherapy is CD276 (B7-H3), an immune checkpoint molecule that is highly overexpressed in many tumors, but minimally expressed in healthy tissues. CD276 is involved in immune escape mechanisms, tumor growth, and metastasis, making it an attractive target for patients unresponsive to PD-1/PD- L1-directed therapies. To address the limitations of T cell-based ICIs, natural killer (NK) cells are being explored as a complementary strategy, as they directly lyse tumor cells through antibody-dependent cellular cytotoxicity (ADCC). Here, we present an Fc-optimized CD276 antibody, 8H8_SDIE, which enhances NK cell reactivity by improving its binding affinity to CD16. In our preclinical studies 8H8_SDIE specifically binds to CD276 on NSCLC cell lines, resulting in significant NK cell activation, characterized by increased expression of CD69 and CD107a, and the secretion of cytotoxic mediators such as IFNγ, perforin, and granzyme B. These findings suggest that 8H8_SDIE may provide a novel therapeutic option for patients with CD276-positive NSCLC, particularly those who have failed to respond to conventional T cell-activating ICIs. By engaging NK cells, this approach could overcome the limitations of PD-1/PD-L1-directed therapies, offering a new way to combat ICI-resistant tumors.